IMPORTANCIA DEL CRECIMIENTO DEL SECTOR CONSTRUCCIÓN EN LA ECONOMÍA Y SOCIEDAD PERUANA - Vargas García, Allan Herminio (2011)
The year 2011 projects that the national construction sector gets an annual growth of 8.3%, driven by the good performance of private investment, which would grow at an estimated rate of 11.8%, while public investment slightly advance at 3.4% by the lowest budget for infrastructure. For its part, the Northern Region grows at an annual rate of 7.6% as a result of the execution of works related to agriculture (irrigation projects), electricity, road infrastructure, real estate projects and mining, among others. For the Central Region is expected to grow 8.4% annually at 2011, based on the development of major projects such as construction of the North Port, the second part of the electric train which is scheduled to start this year, the great projects in the hydroelectric sector like Chaglla highlighting, the large real estate projects, construction of shopping centers, road infrastructure, among others. Also, the South Region is expected to grow 8.9% in 2011, compared with 22.5% of the previous year, the slowdown is due to the missing works of South Interoceanic Highway in this year, and the decline in public investment in infrastructure. However, the implementation of major projects related to natural gas, mining, infrastructure, tourism infrastructure and construction of large shopping centers and housing projects, also influence the growth.